2022
DOI: 10.3390/cancers14235798
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of NCOR2 Inhibits Cell Proliferation via BDNF/TrkB/ERK in NF1-Derived MPNSTs

Abstract: (1) Background: malignant peripheral nerve sheath tumours (MPNSTs) are aggressive Schwann cell-derived sarcomas with dismal prognoses. Previous studies have shown that nuclear receptor corepressor 2 (NCOR2) plays a vital role in neurodevelopment and in various tumours. However, the impact of NCOR2 on the progression of MPNST remains unclear. (2) Methods: by GEO database, MPNST tissue microarray, and NF1-related tumour tissues and cell lines were used to explore NCOR2 expression level in the MPNSTs. The role an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…NCOR2 encodes for a poorly characterized corepressor, which induces gene downregulation through epigenetic modification of DNA 20 . Further, NCOR2 has been shown to contribute to tumor cell proliferation and resistance to hormone therapy 20–22 . To date, 3 different HMGA2::NCOR2 fusion types have been described, including, in decreasing order of frequency: (1) 5’ HMGA2 exons 1 to 3 fused to 3’ NCOR2 exons 16 to 49; (2) 5’ HMGA2 exons 1 to 3 fused to 3’ NCOR2 exons 20 to 49; (3) 5’ HMGA2 exons 1 and 2 fused to 3’ NCOR2 exons 16 to 49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCOR2 encodes for a poorly characterized corepressor, which induces gene downregulation through epigenetic modification of DNA 20 . Further, NCOR2 has been shown to contribute to tumor cell proliferation and resistance to hormone therapy 20–22 . To date, 3 different HMGA2::NCOR2 fusion types have been described, including, in decreasing order of frequency: (1) 5’ HMGA2 exons 1 to 3 fused to 3’ NCOR2 exons 16 to 49; (2) 5’ HMGA2 exons 1 to 3 fused to 3’ NCOR2 exons 20 to 49; (3) 5’ HMGA2 exons 1 and 2 fused to 3’ NCOR2 exons 16 to 49.…”
Section: Discussionmentioning
confidence: 99%
“…20 Further, NCOR2 has been shown to contribute to tumor cell proliferation and resistance to hormone therapy. [20][21][22] To date, 3 different HMGA2:: NCOR2 fusion types have been described, including, in decreasing order of frequency: (1) 5' HMGA2 exons 1 to 3 fused to 3' NCOR2 exons 16 to 49; (2) 5' HMGA2 exons 1 to 3 fused to 3' NCOR2 exons 20 to 49; (3) 5' HMGA2 exons 1 and 2 fused to 3' NCOR2 exons 16 to 49. These fusions are predicted to produce a functional chimeric protein retaining the DNA-binding domains of HMGA2 and most functional and interaction domains of NCOR2.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptor core suppressor 2 (NCOR2) knockdown can inhibit NF1-derived MPNST cell proliferation through diminished BDNF/TrkB/ERK signaling, which indicate the crucial role of BDNF in the progress of NF1 [29] . Therefore, we performed BDNF immunohistochemical staining of neurofibroma tissues and found that trunk neurofibroma tissues expressed significantly less BDNF than head NF, as demonstrated by BDNF immunostaining index ( Fig.…”
Section: Resultsmentioning
confidence: 99%